Antioxidant and neuroprotective activities of essential oil, isolated from Chinese herb pairs of Angelica sinensis and Sophora flavescens - Aiyun Li, Linna Han, Chun Chao Han (Journal of Applied Pharmaceutical Science)
The antioxidant and neuroprotective activities of essential oil (EO), isolated from Chinese herb pairs of Angelica sinensis and Sophora flavescens were studied in this paper. EO significantly improved the outcome in rats after cerebral ischemia and reperfusion in terms of neurobehavioral function. EO treatment decreased the levels of tumor necrosis factor alpha, interleukin 1 beta and oxidative stress. Our results had showed that EO was a potent neuroprotective medicine.
Keywords: Angelica sinensis, Sophora flavescens, Chinese herb pairs, essential oil.